Derivative tasks proposed by techers in training - Vargas González, María Fernanda (2021)
The tasks are fundamental elements in the process of teaching and learning of Mathematics and consequently, the design and selection of these. The present work focuses on characterizing a set of tasks proposed by teachers in training and focused on the derivative of a function at one point, as part of a broader investigation in which we address the meaning that teachers attribute to this topic. We employ the method of content analysis provided with a system of categories that allow us to analyze revealed elements of the meaning of the derivative as well as the cognitive demand encouraged for each of the tasks. We noticed a clear predominance of tasks with low cognitive demand in which the most involved content is the calculation of maxima and minima of a function.